Risks in human development in ethnic communities of the Republic of Tuva (1999–2021) - Balakina, Galina F. (The New Research of Tuva, 2022)
The article examines how members of ethnic communities of the Republic of Tuva assess and act upon the issues of healthcare, level of education, advanced training, provision for the future development of the whole family, including themselves. A special focus is made on understanding risks for human development and minimizing those risks. Our study draws upon official statistics for the years 2000-2021, also making use of the studies carried out from 1999 to 2021 where the author was a team member or the project leader. In recent years, poor salaries and a decrease in real wages have been to blame for the failure to provide a rise in human development for a significant part of the population of the Republic of Tuva. A risk of worsening inter-ethnic relations due to persistently high competition for access to social services and other benefits has so far been neutralized by rising levels of tolerance and low numbers of non-indigenous population. While high and explicit in 1990s, tension in inter-ethnic relations has been gradually easing and stayed latent throughout 2000s. It has persisted up to 2021, although on the whole Tuva’s main ethnicities – Tuvans and Russians – have been interacting in a positive key. Nevertheless, the latent inter-ethnic tension is to blame for the departure of some of those belonging to minority ethnicities from the region, in the search of a more compatible ethnocultural environment and more advantageous social and economic atmosphere for their development. Tuvans see ethnically compact settlement, weak focus on federal identity and preserving survival traditions as pre-requirements for ethnic stability and supporting human development in their own way.